Historicizing entrepreneurial networks. (5th February 2020) - Hollow, Matthew
Abstract: Research summary: In recent years, there has been increased interest in the role of context in different entrepreneurial processes. This article builds on this line of research by deploying a microhistorical‐informed approach to contextualize and make sense of the ways in which the correspondence network of the nineteenth‐century British entrepreneur, Isaac Holden, changed over time. In the process, it contributes to our understanding of entrepreneurial networks by illustrating: (a) how networking activities take place through specific communication platforms with their own socio‐technical qualities; (b) how entrepreneurs have the capacity to actively shape and co‐create the context within which their networking activity takes place; and (c) how entrepreneurial networking activity can take place in conjunction with—or as a result of—networking activity in other social movements. Managerial Abstract: For entrepreneurs, having an effective network of trusted contacts can be the difference between success and failure. But what happens to these relationships when (or if) the entrepreneur achieves commercial success? Do they change? This article advances our understanding in this respect by providing an in‐depth analysis of how, and why, the personal network of Isaac Holden—a British wool manufacturing entrepreneur from the Victorian era—changed over time. In the process, it provides interesting insights into how political, social, cultural, and technological factors have the capacity to shape the way that entrepreneurial networks change and evolve over time.